2018
DOI: 10.1515/med-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

The CCR5-Delta32 genetic polymorphism and HIV-1 infection susceptibility: a meta-analysis

Abstract: AbstractThe CC chemokine receptor 5 (CCR5) is a chemokine receptor which is widely expressed in several immune cells involved in the inflammatory responses. Previous published studies revealed the relation of the CCR5 gene (CCR5-delta32) with the risk of HIV-1 infection, but the results are debatable and inconclusive. Here by meta-analysis, we have systematically evaluated the relation between the CCR5-delta32 polymorphism and the risk of HIV-1 infection. A comprehensive search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Combining data from WES and TaqMan assay, we found that heterozygotes are more frequent in 221 patients with severe COVID-19 than in controls (P GT = 0.027) (Table 3). We also verified the frequency of 32 bp deletion (CCR5-Delta32, rs333), which was already associated with HIV resistance [15] using our 147 COVID-19 hospitalized patients and an Italian cohort of controls from public exomes data of 1095 Italian individuals (Network for Italian Genomes) [23]. No significant difference of frequency of CCR5-Delta32 was observed between controls (10.22%) and COVID-19 cases (10.20%), (P = 0.99; OR = 0.99, 95% CI: 0.57-1.73).…”
Section: Coding Variants In Ccr5mentioning
confidence: 52%
“…Combining data from WES and TaqMan assay, we found that heterozygotes are more frequent in 221 patients with severe COVID-19 than in controls (P GT = 0.027) (Table 3). We also verified the frequency of 32 bp deletion (CCR5-Delta32, rs333), which was already associated with HIV resistance [15] using our 147 COVID-19 hospitalized patients and an Italian cohort of controls from public exomes data of 1095 Italian individuals (Network for Italian Genomes) [23]. No significant difference of frequency of CCR5-Delta32 was observed between controls (10.22%) and COVID-19 cases (10.20%), (P = 0.99; OR = 0.99, 95% CI: 0.57-1.73).…”
Section: Coding Variants In Ccr5mentioning
confidence: 52%
“… 94 As for the meta-analysis by Ni et al, it also evaluated only Indel Δ32 from 24 case–control studies selected without language restriction in the final sample, in the temporal cut from 1996 to 2018, presenting results that this mutation may confer a possible protective role against HIV-1, both to susceptibility and disease severity. 95 Thus, the data configuration can be defined with contrasting aspects between the aforementioned reviews from their population approaches and selection methods.…”
Section: Discussionmentioning
confidence: 99%
“…(F) SDOH shape HIV outcomes for several generations through three types of intergenerational influence. 67,69,[134][135][136][137] (G) SDOH shape the clustering of multiple cooccurring epidemics, which amplifies exposures and susceptibilities associated with increased HIV transmission. 25,138,139 (H) Social injustice shapes HIV inequities directly and in interaction with systematic differences in other SDOH.…”
Section: Unjust Social Processes Shape Sdoh Mechanisms To Produce Hea...mentioning
confidence: 99%